2017
DOI: 10.1002/ece3.3705
|View full text |Cite
|
Sign up to set email alerts
|

Are there morphological and life‐history traits under climate‐dependent differential selection in S TunesianDiplotaxis harra(Forssk.) Boiss. (Brassicaceae) populations?

Abstract: Adaptation of morphological, physiological, or life‐history traits of a plant species to heterogeneous habitats through the process of natural selection is a paramount process in evolutionary biology. We have used a population genomic approach to disentangle selection‐based and demography‐based variation in morphological and life‐history traits in the crucifer Diplotaxis harra (Forssk.) Boiss. (Brassicaceae) encountered in populations along aridity gradients in S Tunisia. We have genotyped 182 individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Sarg. Authors Oberprieler et al 34 reported that using three methods (Mcheza, BayeScan, and Samβada) 732 AFLP loci screened revealed only 1.6% (full dataset) and 0.4% (reduced data set) of all loci were found to be under selection in Diplotaxis harra (Forssk.) Boiss.…”
Section: Discussionmentioning
confidence: 99%
“…Sarg. Authors Oberprieler et al 34 reported that using three methods (Mcheza, BayeScan, and Samβada) 732 AFLP loci screened revealed only 1.6% (full dataset) and 0.4% (reduced data set) of all loci were found to be under selection in Diplotaxis harra (Forssk.) Boiss.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regional adaptive signatures can obfuscate adaptive patterns on a global scale. Several creative solutions to these challenges have been developed, including restricting focus to population samples with limited population structure (11,12), distilling multidimensional relationships among traits or climatic parameter to primary axes of variation (13,14), and sampling across replicate environmental gradients to assess evolutionary convergence (8,15).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, plants of genus Diplotaxis provided supporting evidence for this traditional use as they exhibited anti-inflammatory [ 11 , 12 , 13 ] and antioxidant/antiradical [ 13 , 14 , 15 ] activities since inflammation and oxidative stress are linked to inflammatory movement disorders, including rheumatoid arthritis [ 16 , 17 , 18 ]. Genus Diplotaxis includes edible and medicinal plants [ 12 , 19 , 20 ] of about 30 species, mainly distributed in Central Europe, the Mediterranean region [ 21 ], and Southwest Asia [ 22 ], including Saudi Arabia [ 23 ]. Phytochemical investigations on the herbs of genus Diplotaxis , including Diplotaxis harra , have been disclosed the presence of flavonoids [ 11 , 24 , 25 , 26 , 27 ], isothiocyanate-releasing glucosinolates [ 28 , 29 ], phenolic acids [ 19 ], and phytosterols [ 15 ].…”
Section: Introductionmentioning
confidence: 99%